Khandut revisited: Monuments, shrines, and newly discovered rock art in Wakhan District. Issue 2 (October 2018) - Mock, John
Abstract : In 1972, a brief article titled "Khandud, Village de la Vallée du Wakhan" appeared in Afghanistan 25. The subsequent decades of conflict precluded any follow-up research in Wakhan. The current article, based on field work from 2004 to 2016, examines the present condition of the sites described in 1972, offers a revised analysis of their significance, and introduces newly discovered rock art that connects Wakhan with the Saka culture of Central Asia and illustrates indigenous traditions of the Pamir-Hindukush ethnolinguistic region.